Numerical Tokamak Turbulence calculations on the CRAY T3E - Lynch, V. E.; Leboeuf, J-N.; Carreras, B. A.; Alvarez, J. D.; Garcia, L. (Proceedings of the 1997 ACM/IEEE conference on Supercomputing, 1997)
Full cross section calculations of ion-temperature-gradient-driven turbulence with Landau closure are being carried out as part of the Numerical Tokamak Turbulence Project, one of the U. S. Department of Energy's Phase II Grand Challenges. To include the full cross section of a magnetic fusion device like the tokamak requires more memory and CPU time than is available on the National Energy Research Scientific Computing Center's (NERSC's) shared-memory vector machines such as the CRAY C90 and J90. Calculations of cylindrical multihelicity ion-temperature-gradient-driven turbulence were completed on NERSC's 160-processor distributed-memory CRAY T3E parallel computer with 256 Mbytes of memory per processor. This augurs well for yet more memory and CPU intensive calculations on the next-generation T3E at NERSC. This paper presents results on benchmarks with the current T3E at NERSC. Physics results pertaining to plasma confinement at the core of tokamaks subject to ion-temperature-gradient-driven-turbulence are also highlighted. Results at this resolution covering this extent of physical time were previously unattainable. Work is in progress to increase the resolution, improve the performance of the parallel code, and include toroidal geometry in these calculations in anticipation of the imminent arrival of a fully configured, 512-processor, T3E-900 model.